Formulation and Evaluation of Herbal Hair Growth Oil Using Flower Extract of Lantana camara Linn - Patel, Rachana (International Journal of Pharmaceutical & Biological Archive, 2025)
The present study was designed to formulate and evaluate a herbal hair growth oil incorporating the flower extract of Lantana camara Linn., a plant traditionally known for its diverse pharmacological activities. Fresh flowers were collected, identified, and authenticated, followed by extraction using ethanol–water (1:1) through maceration. The obtained extract was subjected to preliminary phytochemical screening, which confirmed the presence of alkaloids, glycosides, flavonoids, phenols, saponins, tannins, steroids, and triterpenoid compounds known to exert antioxidant, anti-inflammatory, and hair growth-promoting effects. The herbal hair oil was formulated by incorporating the extract with supportive herbal ingredients such as Hibiscus flowers, curry leaves, almond oil, coconut oil, rose oil, and vitamin E, thereby enhancing both therapeutic and cosmetic value. The prepared oil was evaluated for organoleptic and physicochemical parameters including pH, viscosity, acid value, refractive index, specific gravity, and irritation potential. The results indicated that the oil possessed a greenish-brown color, characteristic odor, a pH of 6.5, acceptable viscosity, specific gravity of 0.97 g/cm3, and an acid value within permissible limits. No irritation was observed upon topical application, confirming its safety. The observed phytochemical constituents were considered responsible for the potential hair growth activity. The overall evaluation demonstrated that the herbal hair oil formulation was stable, safe, and effective, suggesting its potential as a natural alternative to synthetic hair growth products. This work highlights the significance of integrating traditional herbal knowledge with scientific validation to develop efficacious hair care formulations